The invention of wings [compact disc, unabridged] - Kidd, Sue Monk (Penguin Audio, 2014)
On Sarah's eleventh birthday, she is given ownership of ten-year-old Handful, who is to be her handmaid. We follow their remarkable journeys over the next 35 years, as both strive for a life of their own, dramatically shaping each other's destinies and forming a complex relationship marked by guilt, defiance, estrangement and the uneasy ways of love.